Research and writing in international relations - Spray, Sharon (Pearson, 2012)
Research and Writing in International Relations offers the step-by-step guidance and the essential resources needed to compose political science papers that go beyond description and into systematic and sophisticated inquiry. This text focuses on areas where students often need help finding a topic, developing a question, reviewing the literature, designing research, and last, writing the paper. Including current and detailed coverage on how to start research in the discipline's major subfields, Research and Writing in International Relations gives students a classroom-tested approach that leads to better research and writing in introductory and advanced courses.